The EMG activity and mechanics of the running jump as a function of takeoff angle - Kakihana, W.; Suzuki, S. (2001)
To characterize the electromyographic (EMG) activity, ground reaction forces, and kinematics were used in the running jump with different takeoff angles. Two male long jumpers volunteered to perform running jumps at different approach speeds by varying the number of steps (from 3 to 9) in the run-up. Subject TM achieved a greater vertical velocity of the center of gravity (CG) at takeoff for all approach distances. This jumping strategy was associated with greater backward trunk lean at touchdown and takeoff, a lesser range of motion for the thigh during the support phase, more extended knee and ankle angles at touchdown, and a more flexed knee angle at takeoff. Accompanying these differences in kinematics, TM experienced greater braking impulses and lesser propulsion impulses for the forward-backward component of the ground reaction force. Furthermore, TM activated mainly the rectus femoris, vastus medialis, lateral gastrocnemius, and tibialis anterior, while if rarely activated the biceps femoris from just before contact to roughly the first two-thirds of the support phase. These results indicate that TM used a greater takeoff angle in the running jump because he enabled and sustained a greater blocking effect via the coordination patterns of the muscles relative to the hip, knee, and ankle joints. These findings also suggest that the muscle activities recorded in the present experiment are reflected in kinematics and kinetics. Further, the possible influence of these muscle activities on joint movements in the takeoff leg, and their effect on the vertical and/or horizontal velocity of the jump are discussed. J Electromyogr Kinesiol 2001 Oct;11(5):365-72